2020
DOI: 10.21037/tlcr.2019.12.15
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal mesothelioma

Abstract: Malignant peritoneal mesothelioma (MPM) is a rare and lethal disease of the peritoneal lining, with high variability in biologic aggressiveness. Morbidity and mortality of the disease are related to progressive locoregional effects within the abdominal cavity, such as distention, pain, early satiety, and decreased oral intake that can ultimately lead to bowel obstruction and cachexia. The standard of care for patients with resectable disease remains cytoreductive surgery and hyperthermic intraperitoneal chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 59 publications
2
58
0
10
Order By: Relevance
“…At present, cytoreductive surgery (CRS) combined with HIPEC as the rst-line treatment of MPM has been proved to improve the prognosis of MPM patients [36][37][38][39][40]. A systematic review and meta-analysis showed patients receiving CRS and HIPEC had a median survival time of 29.5-100 months, much longer than that of untreated patients [41].…”
Section: Discussionmentioning
confidence: 99%
“…At present, cytoreductive surgery (CRS) combined with HIPEC as the rst-line treatment of MPM has been proved to improve the prognosis of MPM patients [36][37][38][39][40]. A systematic review and meta-analysis showed patients receiving CRS and HIPEC had a median survival time of 29.5-100 months, much longer than that of untreated patients [41].…”
Section: Discussionmentioning
confidence: 99%
“…There are stages I, II, and III, with the corresponding five-year survivals of 87%, 53%, and 29%, respectively. This novel staging system allows better prognostic stratification [ 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 3 main histologic subtypes of malignant mesothelioma are epithelioid, biphasic, and sarcomatoid, with a median survival of 19, 12, and 4 months, respectively, for pleural mesothelioma 5 . The overall 5‐year survival is significantly better for patients with peritoneal mesothelioma, and these patients tend to have predominantly epithelioid histology 6 …”
Section: Introductionmentioning
confidence: 99%